ANCIENT ARABIC MANUAL AL AMWAL; ABU UBAID ISLAMIC ECONOMIC PHILOLOGY & THOUGHT REVIEW ON PUBLIC FINANCE - Uus Rustiman (Yayasan Education and Social Center, 2023)
The discussion of ancient texts is attractive, especially literacy texts in the world of Islamic Civilization History, because it does not rule out the possibility that the values ​​and theories can explain complex problems, especially in the study of economics. One of the texts that discuss the issue of public finance in classical Islam is the Al Amwal manuscript by Abu Ubaid Al-Qasim bin Sallam bin Abdillah Al-Adib Al-Faqih Al-Muhadits (157 H / 774 M - 224 H / 838 M) or more known as Abu Ubaid, a productive Islamic scholar. The Al Amwal manuscript is Abu Ubaid's attempt to find various principles and principles of the concept of the public financial system in various Qur'anic verses and the hadiths of the Prophet Muhammad Sallallahu' Alayhi Wasallam and Atsar Shahabat. The research method used in this paper is the philology method, which is a research method to reveal the contents in the form of text in the manuscript, which is reviewed by historical approaches and Islamic economic studies. In this case, the philology method is used to reveal the contents in the form of text in the Al AMwal manuscript by Abu Ubaid and reviewed by historical approaches and Islamic economic studies. The book of Al Amwal illustrates that Abû 'Ubaid did not give his views on a case if he did not find a foundation in the al-Qur'an and al-Hadith. Even so, he gave the maqâsid any-shari'ah a place to carry out legal provisions. 'Tha' Ubaid thought in Al Amwal is a reference in modern economic development, even based on the analysis of The Wealth of Nations contemporary Muslim economic thinker Adam Smith with his work